Bibliometric analysis on global Behçet disease publications during 1980–2014: is there a Silk Road in the literature?. (22nd August 2016) - Şenel, E.; Demir, E.; Alkan, R.M.
Abstract: Background: Behçet disease (BD) is a chronic and multisystemic vasculitis characterized with recurrent oral and genital ulcers, uveitis, arthritis and skin manifestations. The highest prevalence of the disease has been reported in regions historically involved in the Silk Road routes. Objective: We aimed to analyse Behçet literature and evaluate whether there is a concordance between ancient Silk Road regions and the distribution of publication productivity. Methods: The bibliometric analysis of the publications published during 1980–2014 using Thomson Reuters Web of Science database was performed. We generated infographics of productivity and also analysed the correlations among economical productivities, technological advancement levels and humanity index and productivity performances of 78 countries in Behçet literature. Results: Turkey ranked first in Behçet literature with 1837 articles followed by Japan and the USA. Turkey, Tunisia and Israel occupied the first three places in productivity. Significant correlations were noted between 2014 gross economic and technological indices and publication numbers of the countries. We found that European countries had high productivity, although they had low prevalence of BD. We detected no concordance between the productivity density of the countries and the ancient Silk Road routes. Conclusion: Most publications were reported from developed countries although undeveloped or developing countries had higher prevalence of BD. Physicians in undeveloped and developing countries should be supported and encouraged to perform novel studies on BD.